Ensuring the Reliability of Conclusions in the Expert's Statement in the Course of a Forensic Construction Investigation - A. Yu. Butyrin; Z. V. Trifonova (Теория и практика судебной экспертизы)
The appointment and production of forensic investigation is one of the most common procedural actions in modern legal proceedings, along with the evaluation of the expert witness statement by the body (person) that ordered the examination. The article deals with a number of problems associated with evaluating of the expert witness statement reflecting the progress and results of a forensic construction investigation. Reliability is the most complex and contradictory criterion in the evaluation of expert testimony. Taking into account the courts' constantly growing need for construction forensics expert services, on the one hand, and insufficient elaboration of this assessment criterion for this kind of expert evidence, on the other hand, the authors explore the subject in depth and present their interpretation of the notion of «reliability», as applied to the evaluation of construction forensics expert statements.